2013
DOI: 10.1088/2041-8205/766/2/l17
|View full text |Cite
|
Sign up to set email alerts
|

WHAT DETERMINES THE DENSITY STRUCTURE OF MOLECULAR CLOUDS? A CASE STUDY OF ORION B WITH HERSCHEL

Abstract: A key parameter to the description of all star formation processes is the density structure of the gas. In this letter, we make use of probability distribution functions (PDFs) of Herschel column density maps of Orion B, Aquila, and Polaris, obtained with the Herschel Gould Belt survey (HGBS). We aim to understand which physical processes influence the PDF shape, and with which signatures. The PDFs of Orion B (Aquila) show a lognormal distribution for low column densities until A V ∼ 3 (6), and a power-law tai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
323
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 252 publications
(372 citation statements)
references
References 49 publications
(61 reference statements)
47
323
0
Order By: Relevance
“…4, bottom) in which the IRDC is embedded indeed shows a log-normal part plus a power-law tail, similar to what was found for star-forming clouds (e.g. Kainulainen et al 2011b;Schneider et al 2013).…”
Section: Pdfs From Dust Continuumsupporting
confidence: 78%
See 1 more Smart Citation
“…4, bottom) in which the IRDC is embedded indeed shows a log-normal part plus a power-law tail, similar to what was found for star-forming clouds (e.g. Kainulainen et al 2011b;Schneider et al 2013).…”
Section: Pdfs From Dust Continuumsupporting
confidence: 78%
“…Federrath & Klessen 2013, and references therein). Observational studies, based on near-IR extinction or Herschel dust column density maps, showed that the PDF of star-forming clouds has a log-normal distribution for low column densities and a power-law tail for higher column densities, where the power-law tail is either interpreted as due to external pressure (Kainulainen et al 2011b), self-gravity (Froebrich & Rowles 2010;Schneider et al 2013Schneider et al , 2015, or a combination of both (Tremblin et al 2014). Numerical simulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We do not have direct access to the 3D (volume) density from observations-only to the 2D (column) density distribution (Berkhuijsen & Fletcher 2008;Kainulainen et al 2009;Lombardi et al 2011;Schneider et al 2012Schneider et al , 2013Hughes et al 2013;Kainulainen & Tan 2013;Berkhuijsen & Fletcher 2015;Schneider et al 2015). However, one can estimate the 3D density dispersion and the 3D density PDF by extrapolating the 2D density information given in the plane of the sky to the third dimension (along the line of sight), assuming isotropy of the clouds (Brunt et al 2010a(Brunt et al , 2010bKainulainen et al 2014).…”
Section: Density Pdf and Conversion From Twomentioning
confidence: 99%
“…Those PDFs have been characterised by a lognormal at low column densities which becomes dominated by a power law tail at the high end (Kainulainen et al 2009;Schneider et al 2013Schneider et al , 2015Benedettini et al 2015). The presence of the lognormal component has, however, been questioned by Lombardi et al (2015) who argue that column density PDFs of molecular clouds can be accounted for entirely by truncated power laws.…”
Section: Relationship To Unbound Starless Coresmentioning
confidence: 99%